Comparison of 2% Rebamipide and 0.1% Sodium Hyaluronate in the Treatment of Dry Eye - Ashok K Sharma; Swati Sharma; Hans Raj Sharma (Dr. Annil Mahajan, 2021)
Background: Dry eye disease is a multifactorial disease with varying presentations ranging from minor discomfort to sight threatening complications. Different drugs are used to treat dry eye and act on different layers of the tear film. Rebamipide is a new emerging drug that specifically addresses mucin deficient dry eye. Purpose: To evaluate the efficacy of 2% rebamipide and to compare it with 0.1% sodium hyaluronate in the treatment of dry eye disease. Material and Methods: 130 patients visiting the eye OPD of a tertiary care hospital in North India with dry eye disease were enrolled and divided randomly into two groups of 65 patients each. One group was prescribed 2% rebamipide eye drops 4 times a day and the other was prescribed 0.1% sodium hyaluronate 6 times a day for 6 weeks. Schirmer's test values, tear film breakup time (TBUT), Lissamine green staining score and a dry eye related questionnaire were evaluated at 2, 4 and 6 weeks. Results: The difference between the results of the two groups was found to be statistically significant (p value <0.05) at 6 weeks of therapy. Conclusion: Rebamipide proved to be better than sodium hyaluronate in reducing the symptoms and improving clinical signs like Schirmer's values, TBUT and lissamine staining score when used for up to 6 weeks and may emerge as 1st line treatment for dry eye disease in near future.